anonymous
  • anonymous
i have a couple of math problems to solve anyone care to help me one on one plz...i really appreciate it
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
1 Attachment
anonymous
  • anonymous
\[h(x)=\sqrt{4x+8}\] 4x+8≥0 4x≥-8 x≥-2 D:(x I x≥-2, x E R)
anonymous
  • anonymous
I REALLY THANK U FOR HELPING ME OUT

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
you're welcome
anonymous
  • anonymous
I GET CONFUSED BECAUSE I HAVENT DONE THIS MATH IN A LONG WHILE..CAN U FINISH HELPING ME PLZ...ONLY IF U CAN
anonymous
  • anonymous
ok number 11 a) f(x) - g(x) + h(x) just plug the functions f(x), g(x), and h(x) you'll get the result = -2x^2 + 27x -4
anonymous
  • anonymous
b) g(x)/h(x) again, just plug g(x) and h(x) (10x^2 - 15x)/5x = 2x-3
anonymous
  • anonymous
im confused on number 11a
anonymous
  • anonymous
i inserted f g h
anonymous
  • anonymous
but i got: \[f(23x-4) - G(85) + h(5X)\]
anonymous
  • anonymous
f(x) - g(x) + h(x) = (8x^2 +7x-4) - (10x^2 -15x) + (5x) 8x^2 +7x-4 - 10x^2 + 15x + 5x
anonymous
  • anonymous
where did you get that? you just need to substitute f(x) with 8x^2 +7x-4 substitute g(x) with 10x^2 -15x and substitute h(x) with 5x
anonymous
  • anonymous
i got confused ...now i see it...ughhhhh *sign*
anonymous
  • anonymous
1 Attachment
anonymous
  • anonymous
number 12 is about function composition g(f(3)) first, find f(3) f(x) = 8x^2 +7x-4 so f(3) = 8(3)^2 + 7(3) -4 f(3) = 8(9) + 21 -4 f(3) = 72+21-4 f(3) = 89 therefore g(f(3)) = g(89) g(x) = 10x^2 -15x g(89) = 10(89)^2 - 15(89)
anonymous
  • anonymous
number 12 is confusing "O
anonymous
  • anonymous
13) because M is the midpoint, AM=MB 2x^2 - 10x + 15 = x^2 - 2x + 3 x^2 - 8x + 12 = 0 (x-6)(x-2) x = 6 or x=2
anonymous
  • anonymous
this is an article from wikipedia , related to number 12 http://en.wikipedia.org/wiki/Function_composition
anonymous
  • anonymous
thanks
anonymous
  • anonymous
1 Attachment
anonymous
  • anonymous
14) AC is an angle bisector, therefore angle BAD = angle CAD x^2 = 5x + 24 x^2 - 5x - 24=0 (x-8)(x+3) x=8 or x=-3
anonymous
  • anonymous
15) BAD is a right angle 4x+8+7x+5 = 90 degree 11x + 13 = 90 11x = 77 x=7
anonymous
  • anonymous
16) 8x+12 + 2x+8 = 180 degree 10x + 20 = 180 10x = 160 x= 16
anonymous
  • anonymous
1 Attachment
anonymous
  • anonymous
17) x^2 = 6x-8
anonymous
  • anonymous
for number 12 how did we get 8 if the problem is f(x) = 3x -4 and g(x) = x to the 2nd -5 you dont have to redo the problem just need to know how 8 got there
anonymous
  • anonymous
oh, sorry, i did it wrong, i didnt see the f(x) and g(x) in number 11 and 12 are different, i'll do it again
anonymous
  • anonymous
ok thanks
anonymous
  • anonymous
f(x) = 3x -4 and g(x) = x^2 - 5 f(3) = 3(3) - 4 = 9-4 = 5 because f(3) = 5, g(f(3)) = g(5) g(5) = (5)^2 - 5 = 25-5 = 20
anonymous
  • anonymous
thank you very much for correcting it ")
anonymous
  • anonymous
1 Attachment
anonymous
  • anonymous
19, because it's an iscoceles triangle, angle C must be the same as angle A. a triangle has an angle of 180 degree, so : A + B + C = 180 degree 2x^2 + x^2 + 2x^2 = 180
anonymous
  • anonymous
1 Attachment
anonymous
  • anonymous
god ur good at this
anonymous
  • anonymous
can i borrow ur brains for my finals...lol ")
anonymous
  • anonymous
this is for number 20
1 Attachment
anonymous
  • anonymous
lol, not really good, actually, this is kinda like SAT problems
anonymous
  • anonymous
damn then i am dumb "(
anonymous
  • anonymous
1 Attachment
anonymous
  • anonymous
you just need to keep practicing, you'll be good at this. sorry i can't continue this, i gotta go. bye
anonymous
  • anonymous
ok thank u very much for all ur help

Looking for something else?

Not the answer you are looking for? Search for more explanations.